Analysis of Sikidang Crater Tourism Potential and Its Socio-Economic, and Cultural Impact on the Community In Banjarnegara Regency, Central Java - Sholihah, Mar'atus; Rizqina Awaliyah; Muhammad Alfaruqi; Armawati Hidayati; Nasrulloh Muzaki (International Journal of Geography, Social, and Multicultural Education, 2026)
Sikidang Crater is located in the Dieng Plateau, which is located in Banjarnegara Regency, Central Java, Indonesia. The Dieng area itself is famous for its stunning natural scenery and various natural attractions. This article discusses the potential for developing Sikidang Crater as a tourist destination that is a popular tourist destination in Central Java, offering a unique and educational experience for every visitor. Tourist Activities in Sikidang Crater In addition to enjoying the scenery and learning about volcanic phenomena, Sikidang Crater also offers various interesting tourist activities that can be enjoyed by visitors. Sikidang Crater in Dieng has a significant impact on the social and economic life of the local community. Economically, Sikidang Crater is a source of income for the community through the tourism and agricultural sectors. Socially, the community around Sikidang Crater has unique traditions and beliefs related to the crater, and has a high level of tolerance for other beliefs. The existence of the Sikidang Crater Dieng tourist attraction provides many benefits for the community and visitors, such as preserving local culture, increasing environmental awareness and becoming a means of natural education. However, on the other hand, it also has negative impacts, such as the influence of foreign cultures, environmental damage and the potential for decreased attention to formal education.